Using numerical simulation to investigate the effect of layer thickness on residual stress and warping of specimens made of ABS - Alzyod, Hussein; Ficzere, Péter (Design of Machines and Structures, 2022)
Fused Filament Fabrication (FFF) is an additive manufacturing technology that is used to create a wide range of parts and applications. Along with its benefits, there are some challenges regarding the printed parts’ mechanical properties, which are associated with printing parameters like layer thickness, infill density, print speed, and nozzle temperature. Experimentally investigation of these pamperers is costly and time-consuming. Some simulations are available to use the numerical solution in the investigation. This work used Digimat-AM simulation to investigate the effect of layer thickness on the residual stress and warping deformation of printed ABS parts.